Students’ self-regulation and critical thinking in learning e-commerce through social networking site - Linggu, Jacquelin S. (2015)
This study aims to analyse the effect of social learning environment through Social Networking Site (SNS) towards students’ Self-Regulation (SR), Critical Thinking (CT), and performance in learning E-Commerce subject. Initially, this study has identified the self-regulation and critical thinking levels among students. The study also investigates the relationship between students’ self-regulation, critical thinking skills, and performance when using SNS. Finally, this research has examined how student cultivate self-regulation and critical thinking in learning through SNS. 295 undergraduate students who were taking E-Commerce subjects at a private institution in Kota Kinabalu were selected using cluster random sampling technique. These students were involved in determining their self-regulation and critical thinking level. Next, 50 students were selected purposively to involve in a study in analysing the effects of social learning environment through SNS towards students’ self-regulation, critical thinking, and performance in learning E-Commerce. Self-regulated learning was measured using adopted Online Self-Regulation Learning Questionnaire (OLSQ), while critical thinking was measured using adapted California Critical Thinking Skills Test (CCTST) and academic performance was measured using a question exam paper for the E-Commerce subject. The results obtained from post test reveal that selfregulation, critical thinking level, and performance in learning E-Commerce subject have improved after they went through learning process in social learning environment when using SNS. Pearson correlation analysis reveals that there was no significant relationship between self-regulated learning and critical thinking as well as selfregulated learning and academic performance. However, there was a moderate positive correlation between critical thinking and academic performance. Besides, there was a positive pattern of relationship in the process of identifying student’s self-regulated learning, critical thinking, and academic performance when analysed further using crosstabulation analysis that involved partial data. A data mining analysis using decision tree technique was used to project a predictive model that suggests students’ performance based on the percentage of student’s frequency posting of self-regulation and critical thinking messages throughout the discussion in social networking site. The finding also shows that student’s acquire the ability to cultivate self-regulation and critical thinking based on the discussion with an instructor and peers in social networking site. Results also show that student’s academic performance improves, along with self-regulation and critical thinking.